The Effectiveness of Group Guidance with Sociodrama and Group Discussion Techniques on Student Career Planning (Universitas Negeri Semarang, 2018)
This study aimed to determine the influence of group guidance services with socio-drama and group discussion techniques towards students’ career planning in Eighth Grade level of Public Junior High School (SMP Negeri) 1 Mejobo Kudus. The study used Pre-post Control Group research design. Meanwhile, the subjects of this study were the Eighth Grade students of SMP Negeri 1 Mejobo Kudus which amounted to 24 students selected by purposive sampling. The results of the study showed that before the group guidance given to the students, their average percentage of career planning was 79.125% (low category). Then, after the group guidance with socio-drama technique was given, the percentage increased to 96.44% (high category). On the one hand, initially, the career planning level of students before receiving group discussion technique obtained the percentage of 65.13% (low category). Meanwhile, after they received given group guidance, the percentage increased to 78.73 (high category). At last, the discussion of the findings of this study was focused on the effectiveness of group guidance with socio-drama and group discussion techniques towards students’ career planning in Eighth Grade level of Public Junior High School (SMP Negeri) 1 Mejobo Kudus.